Effect of the employees' mental toughness on organizational commitment and job satisfaction: Mediating psychological well-being - Minkyung Lee; Bo-Young Kim (Administrative Sciences, 2023)
This study aims to examine the impact of mental toughness of employees on their psychological well-being, job satisfaction, and organizational commitment. A research model based on structural equation modeling ' developed, and a survey was conducted with 534 office workers in Korean companies to gather the data. The findings indicate that mental toughness has a significant effect on psychological well-being and positively (+) affects organizational commitment and job satisfaction through psychological well-being. The study also reveals that mental toughness has a greater influence on organizational commitment than on job satisfaction. However, the positive effect of job satisfaction was found to increase when psychological well-being was mediated. Consequently, this study recommends that employees' mental toughness be managed effectively to improve their job satisfaction and organizational commitment, leading to enhanced job competency, and reduced turnover intention. These findings are of practical significance to organizational practitioners, as they underscore the importance of fostering mental toughness among employees to promote their well-being and commitment to their work.
Keywords: 350; job satisfaction; organizational commitment; mental toughness; psychological well-being